2013
DOI: 10.1186/1297-9716-44-93
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the immune response to vaccination with an inactivated vaccine associated to bovine neonatal pancytopenia by deep sequencing transcriptome analysis in cattle

Abstract: Bovine neonatal pancytopenia (BNP) is a new fatal, alloimmune/alloantibody mediated disease of new-born calves induced by ingestion of colostrum from cows, which had been vaccinated with a specific vaccine against the Bovine Virus Diarrhoea Virus (BVDV). The hypothesis of pathogenic MHC class I molecules in the vaccine had been put up, but no formal proof of specific causal MHC class I alleles has been provided yet. However, the unique features of the vaccine obviously result in extremely high specific antibod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 59 publications
1
24
0
Order By: Relevance
“…The BM antibody test results against whole BVDV were not significantly different between Bovidec and Bovilis BVD vaccines, suggesting that the differences observed in the Pourquier p80 ELISA were specific to the vaccine brand. The elevated antibody reactivity against whole BVDV observed with the PregSure BVD vaccine is possibly due to increased immunogenicity associated with the specific adjuvant used in this vaccine (Demasius et al, 2013). The PregSure BVD vaccine has recently been withdrawn, due to links with neonatal pancytopenia in calves (Deutskens et al, 2011;Euler et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The BM antibody test results against whole BVDV were not significantly different between Bovidec and Bovilis BVD vaccines, suggesting that the differences observed in the Pourquier p80 ELISA were specific to the vaccine brand. The elevated antibody reactivity against whole BVDV observed with the PregSure BVD vaccine is possibly due to increased immunogenicity associated with the specific adjuvant used in this vaccine (Demasius et al, 2013). The PregSure BVD vaccine has recently been withdrawn, due to links with neonatal pancytopenia in calves (Deutskens et al, 2011;Euler et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Animals, sampling and data collection were identical to those described in our previous study [19]. The study included six lactating and six non-lactating cows ( Table 1).…”
Section: Animals and Samplingmentioning
confidence: 99%
“…Comparative transcriptional profiling of bovine blood leucocytes and macrophages in response to infection using RNAseq and gene expression microarrays showed that RNAseq is superior in detecting differential gene expression because of its increased dynamic range [17,18]. Recently, we demonstrated that RNAseq analysis is remarkably applicable for monitoring the immune response in whole blood of cows subjected to an antigen challenge [19]. The results of our study provided a comprehensive catalogue of transcripts expressed in whole bovine blood and identified transcripts differentially expressed in response to the antigen challenge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 The blood transcriptome has been widely studied for molecular and cellular profiling of the human immune response. 18 In primates, transcriptomic studies have been published for several model species, including 2 macaques: the rhesus macaque (M. mulatta) and the cynomolgus macaque (M. fascicularis). 18 In primates, transcriptomic studies have been published for several model species, including 2 macaques: the rhesus macaque (M. mulatta) and the cynomolgus macaque (M. fascicularis).…”
Section: Introductionmentioning
confidence: 99%